New regulatory perspectives for a developing country: The case of Turkey - (:unkn) unknown (Peter Lang AG, 2016)
In order to achieve good quality regulation, a regulatory impact assessment (RIA) may be necessary. This is particularly the case in developing countries, where poor quality regulation is a challenge. As a developing country, Turkey has some regulatory institutions in certain sectors, but these are somewhat weak and subject to historical concerns with an over-powerful bureaucracy, politicisation and executive influence, and dynamics that create rather than curtail rent-seeking behaviours. Therefore, it might be useful to discuss the possibility of better regulation using a new regulatory perspective. For this purpose, evaluation through a RIA is advised. Here, information about the history and development of regulatory institutions presently operating in Turkey is provided, along with discussion of a new regulatory perspective. © 2016 Peter Lang GmbH. All rights reserved.
Keywords: Regulation; Regulatory impact assessment; Turkey